Quality-based Spatial/Spectral Image Transformation - Herman, N. S.; Hussin, B. (2010)
Remote sensing image plays a very important role for GIS services as one of its important data source. It’s very large volume requirement may lead to latency during data transmission. Several alternative solutions are identified as the solution for the issue. This paper is intended to discuss the effect of image compression technique to allow the reduction of the storage and bandwidth requirement at the same time maintaining the quality of the compressed image. An experiment has been performed towards several multispectral images to foresee the effectiveness of the proposed method. The ongoing study shows promising result especially in terms of storage and image quality.